2021
DOI: 10.7150/thno.58655
|View full text |Cite
|
Sign up to set email alerts
|

GLS-driven glutamine catabolism contributes to prostate cancer radiosensitivity by regulating the redox state, stemness and ATG5-mediated autophagy

Abstract: Radiotherapy is one of the curative treatment options for localized prostate cancer (PCa). The curative potential of radiotherapy is mediated by irradiation-induced oxidative stress and DNA damage in tumor cells. However, PCa radiocurability can be impeded by tumor resistance mechanisms and normal tissue toxicity. Metabolic reprogramming is one of the major hallmarks of tumor progression and therapy resistance. Specific metabolic features of PCa might serve as therapeutic targets for tumor radiosensitization a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 87 publications
1
110
0
Order By: Relevance
“…Primary cultures were not further used past passage 5. The gene expression profiling and functional characterization of the primary cultures including clinical characteristics of enrolled patients was previously published (Mukha et al, 2021). The median age of included patients was determined as being 68 years [range: 62; 76], a median Gleason score of 7 [3 + 3; 5 + 5] and a median PSA level at diagnosis with 8.82 ng/mL [5.14; 38].…”
Section: Primary Prostate Culturesmentioning
confidence: 99%
“…Primary cultures were not further used past passage 5. The gene expression profiling and functional characterization of the primary cultures including clinical characteristics of enrolled patients was previously published (Mukha et al, 2021). The median age of included patients was determined as being 68 years [range: 62; 76], a median Gleason score of 7 [3 + 3; 5 + 5] and a median PSA level at diagnosis with 8.82 ng/mL [5.14; 38].…”
Section: Primary Prostate Culturesmentioning
confidence: 99%
“…Our recent study demonstrated that prostate cancer cells and CSCs, in particular, are addicted to glutamine [ 1 ]. Glutamine is a non-essential amino acid that becomes conditionally essential for fast-proliferating tissues, including cancer.…”
mentioning
confidence: 99%
“…The authors showed that an increase in phosphoribosyl pyrophosphate amidotransferase (PPAT) and PPAT/GLS ratio is required to trigger nitrogen shift towards nucleotide biosynthesis in lung cancer and could be considered as a universal phenomenon in other cancer types apart from colorectal cancer [98]. Moreover, the authors further suggested, contrary to the previous observations, that GLS1 possesses antitumor effect rather than protumoral activity, which would call into question all previous reports showing, for instance, involvement of Gln in cancer cell redox homeostasis [117] or lipogenesis [56] and aspartate [108] metabolism. Thus, it would be interesting to investigate multiple tumors under various conditions and assess whether the tumor heterogeneity could explain the inconsistency between the recent report and previous studies.…”
Section: Glutamine Synthesis Glulmentioning
confidence: 76%